Sistema de distribuição de energia elétrica a dois condutores para atendimento a cargas rurais trifásicas - Fandi, Juliane Cristina de Oliveira (2013)
The use of single-phase medium-voltage grids with one or two wires represents a very widespread alternative in Brazilian electricity sector to supply rural loads, mainly because of the associated low investment when compared to the three-phase power distribution grids. Although such network topologies are capable to meet most of the needs of these facilities, specific features related to the need of using more expressive driving loads by some rural consumers recommend the employment of three-phase motors. Commonly, the solution for the problem has been the replacement of the single-phase branch of the rural consumer by a new branch with three-phase topology which is more expensive and often unfeasible for both the consumer and the distribution utilities. On some occasions, systems to convert the number of phases are also used, all based on power electronics. Given this scenario, this work aims to contribute to the expansion of the electricity market in rural areas, offering a distinct possibility for solving the problem by exploiting the physical topology of the single-phase branches existing in rural facilities to supply the same premises using a new concept to transform the number of phases, based solely on magnetic units. The proposed system of three-phase two-wire supply has its design physical and mathematically analyzed under different load conditions and the supply, and is patterned, computationally simulated and experimentally confirmed to have effectiveness. Based on these principles, the study shows that the proposal presents to be constructively simple, offers low maintenance and requires extremely attractive investments.